Integrasi nilai nilai Al Qur'an dalam pendidikan kewarganegaraan - muhammad; Syamzaimar (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2026)
This study examines the integration of Al-Qur'an values into civic education as a strategic effort to strengthen students’ moral character and civic responsibility. Civic education serves as a fundamental component in developing citizens who not only understand their rights and obligations but also demonstrate ethical awareness and social sensitivity. The incorporation of values derived from the Al-Qur'an, such as justice, trustworthiness, tolerance, and cooperation, contributes to a more holistic and value-based learning process. This research employs a qualitative approach through literature review and conceptual analysis to identify effective methods for embedding these values into teaching materials, instructional strategies, and classroom practices. The findings reveal that such integration enhances students’ comprehension of civic concepts while simultaneously fostering spiritual and moral development. Moreover, it promotes the formation of responsible, ethical, and socially engaged citizens within a diverse society. Therefore, integrating religious values into civic education is essential for achieving a balanced educational framework that supports both intellectual growth and character development.